Medical Necessity as an Ethical Imperative for Equitable Access to Abortion Services in Canada - Dhamanaskar, Roma; Benjamin, Kayla; Keer, Kyra; Chauhan, Nipa (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
The Canadian healthcare system has a rich history of using public funds for medically necessary hospital and physician services, legislated by the Canada Health Act (CHA). Overlapping with this history is the fight for reproductive rights which culminated in the decriminalization of abortion in 1988. Provincial and territorial governments must ensure that residents have “reasonable access” to health services deemed “medically necessary” as per the CHA principle of accessibility; the federal government holds the authority to withhold funding to sub-national governments if violated. We demonstrate that sufficient policy and legislative evidence exists to support abortion as a medically necessary procedure in Canada. We further argue that, as a medically necessary health service, the inequitable landscape of abortion access across Canada requires vast improvements to fulfil the “accessibility” principle. Systemic and geographical barriers, a lack of culturally informed care, unwilling providers, and anti-choice influences complicate abortion access. Though accessibility has been broadened with the introduction of Mifegymiso — the gold standard for medical abortion — this has not solved the problem of access. In this paper, we argue that classifying a procedure as medically necessary, in this case abortion, requires active and sustained policy action to improve equitable access and remove barriers to care. We justify the special status we give abortion through utilitarian and justice reasons, and due to the unique barriers to care faced by patients seeking abortions.